Consumer mobiltity in the Irish health insurance market : determinants, incentives and risk equalisation - Keegan, Conor (Trinity College (Dublin, Ireland). School of Medicine. Centre of Health Policy and Management, 2016)
Consumer choice of, and competition among, insurers is becoming a more common feature of many health insurance systems, internationally. For competition, theoretically, to work as a tool of resource allocation in these markets it is important to consider both the ease of consumer switching and the quality of risk equalisation. Consumers should be able to switch insurers without incurring significant switching costs, of which there can be many. Importantly, where consumers are motivated to switch for reasons of price and quality, insurers will be motivated to compete along these dimensions. Furthermore, absence of (or presence of poor quality) risk equalisation in community rated markets can encourage insurers to risk select profitable (e.g. young and healthy) risks at the expense of unprofitable (e.g. older and sicker) risks. Risk selection can have a number of detrimental competitive effects and the best, and most common, way to mitigate against this behaviour is to organise risk equalisation payments between insurers that reflect consumer risk. This thesis uses the Irish private voluntary health insurance market to explore these issues. While a competitive private health insurance market has been in existence in Ireland for close to 20 years, little is known about the motivations and characteristics of switchers in the market. Furthermore, the evolution of the community rated market, in the absence of, for the most part, any risk equalisation payments resulted in strong incentives for risk selection. This contributed to large risk asymmetry observable between the former state-backed monopoly insurer, the Voluntary Health Insurance Board, and the newer entrants. In 2013, risk equalisation payments commenced, however, no detailed understanding exists in terms of their impact. Moreover, this investigation takes place at a time when serious consideration had been given to expanding the role competitive health insurance financing played in the Irish market. More broadly, empirical analysis of these issues in duplicative voluntary health insurance markets has been very limited to date. Taking the above into consideration, and guided by the construction of a conceptual framework of consumer mobility, this thesis examined, in the context of the Irish health insurance market: consumer-reported motivations for switching, and not switching, insurer -- actual switching behaviour, and -- the performance of the belatedly introduced risk equalisation scheme. These issues were analysed through three quantitative empirical studies each based on three distinct datasets obtained exclusively from the Health Insurance Authority and the Voluntary Health Insurance Board, respectively. A low annual switching rate is reported in the Irish market, estimated at slightly less than four percent. In this regard, a large proportion of consumers appear happy with their health insurer and do not switch for that reason. However, a number of costs to switching were also identified. Most notably, over one in seven consumers cited transaction costs as a reason for not switching while a number of non-rational motivations were also reported. The distribution of switching costs also fell disproportionately on high-risk individuals and this was reflected in lower switching propensities for these groups. When individuals did switch, price was reported as the dominant motivation while quality was considerably less important. Reflecting this, strong price effects were also identified when modelling actual switching behaviour, although price responsiveness decreased with age and prior healthcare utilisation, respectively. Evidence from this thesis also points towards the need to improve risk equalisation design if market asymmetry and selection incentives are to be appropriately addressed. Evidence is also found that the replacement of the current risk equalisation design with one predicated on diagnostic information may be a way to achieve this. Overall, results from this thesis provide much deeper and clearer insights into consumer choice of, and competition between, insurers in the Irish market than has heretofore existed. Particularly, concern over barriers to switching, their distribution in the insured population, and the quality of risk equalisation raise questions over the competitive environment in which the Irish voluntary health insurance market currently operates. A corollary of these empirical findings is that they also question the wisdom, on competitive grounds, of transitioning to a mandatory competing health insurer financing model, a reform that up until very recently was being strongly considered by policymakers.
Keywords: Health Policy, Ph.D.; Ph.D. Trinity College Dublin